PERFORMANCE ANALYSIS OF APIP (GOVERNMENT INTERNAL SUPERVISION APPARATUS) IN REALIZING GOOD GOVERNANCE IN THE INSPECTORATE OF NORTH SUMATRA PROVINCE - Beni Pratama Harahap; Hatta Ridho; Tengku Irmayani (PT. Radja Intercontinental Publishing, 2024)
Good governance is the key to realizing development in a region which can be seen from the compliance of policy makers in implementing government regulations. In order to ensure the realization of good governance, a Government Internal Oversight Apparatus (APIP) was formed which was handled by the Inspectorate through supervisory activities (audits, reviews, evaluations, monitoring and other supervisory activities).This research aims to analyze APIP's efforts to improve and strengthen performance at the North Sumatra Province Inspectorate and the factors underlying APIP to improve and strengthen its supervision. This study uses a qualitative method. Data was collected through interviews and the validity of the data was tested using data triangulation techniques. Data analysis was carried out with the help of performance indicators presented by Moeheriono. The results of the research show that (1) the efforts made by APIP to improve supervision are carried out through providing training for developing the quality of human resources, recruiting employees, optimizing time, integrating Inspectorate data digitally, maintaining websites, submitting additional budgets, and establishing regulations for OPDs that exceed limits. completion time for improvements to evaluation results; (2) the inhibiting factors for improving and strengthening supervision are the lack of quantity and quality of human resources, limited time, lack of facilities, lack of digital integration, insufficient budget, and no special regulations.